2021
DOI: 10.3390/metabo11080543
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-Coenzyme A: Cholesterol Acyltransferase (ACAT) in Cholesterol Metabolism: From Its Discovery to Clinical Trials and the Genomics Era

Abstract: The purification and cloning of the acyl-coenzyme A: cholesterol acyltransferase (ACAT) enzymes and the sterol O-acyltransferase (SOAT) genes has opened new areas of interest in cholesterol metabolism given their profound effects on foam cell biology and intestinal lipid absorption. The generation of mouse models deficient in Soat1 or Soat2 confirmed the importance of their gene products on cholesterol esterification and lipoprotein physiology. Although these studies supported clinical trials which used non-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 105 publications
1
22
1
Order By: Relevance
“…The downstream mechanism by which AUP1 regulates lipid metabolism was studied through multiple integration RNA‐seq analysis of differentially expressed genes involved in lipid storage, CHOL efflux, and CHOL storage (from GSEA). The results presented SOAT1 in the convergence diagram (Figure 5A), which catalyzes the formation of FA‐CE 22 . Further qPCR verification of ACHN and A498 cells after transfection showed that SOAT1 expression decreased significantly with AUP1 knockdown (Figure 5B).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The downstream mechanism by which AUP1 regulates lipid metabolism was studied through multiple integration RNA‐seq analysis of differentially expressed genes involved in lipid storage, CHOL efflux, and CHOL storage (from GSEA). The results presented SOAT1 in the convergence diagram (Figure 5A), which catalyzes the formation of FA‐CE 22 . Further qPCR verification of ACHN and A498 cells after transfection showed that SOAT1 expression decreased significantly with AUP1 knockdown (Figure 5B).…”
Section: Resultsmentioning
confidence: 92%
“…The results presented SOAT1 in the convergence diagram (Figure 5A ), which catalyzes the formation of FA‐CE. 22 Further qPCR verification of ACHN and A498 cells after transfection showed that SOAT1 expression decreased significantly with AUP1 knockdown (Figure 5B ). The Clinical Proteomic Tumor Analysis Consortium database showed increased SOAT1 expression in ccRCC tissues, which gradually increased with the progression of tumor grade (Figure 5C ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The pathogenesis of atherosclerosis in patients with DKD is multifactorial, with both conventional and emerging risk factors playing a role [ 7 ]. Recently, sterol-O-acyltransferase-1, an enzyme that esterifies free cholesterol, the NLRP3 inflammasome pathway and the interleukin-33/ST2 pathway have also been implicated in the atherogenetic process in these patients [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Several previous reports observed greater atherosclerotic burden in the carotid arteries of patients with DKD than in diabetic patients with preserved renal function [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%